2018
DOI: 10.1111/ap.12240
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Client Suicide on Psychologists in Australia

Abstract: Objective: This research aimed to assess the frequency and impact of client suicides on psychologists in Australia. Method: Participants were 178 psychologists who completed an online self-report questionnaire concerning the frequency of occurrence and impact of client suicide. Results: Fifty six (31.5%) participants reported one or more client suicides. Psychologists with more years of experience reported more client suicides. Participants who had experienced a client suicide reported a range of emotional, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
34
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 27 publications
(88 reference statements)
4
34
1
Order By: Relevance
“…The experience of losing a patient to suicide resulted in some practitioners being more accepting of suicide as a possibility (Kleespies et al, 1990; Linke et al, 2002) or having an increased awareness of the limits of their professional ability to prevent suicide (Goldstein & Buongiorno, 1984; Gulfi et al, 2010; Ting et al, 2006). Other studies detected increased acceptance of suicide itself (Finlayson & Graetz Simmonds, 2016) or feelings of understanding or acceptance of suicide as an option (Rothes, Scheerder, Van Audenhove, & Henriques, 2013; Ting et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The experience of losing a patient to suicide resulted in some practitioners being more accepting of suicide as a possibility (Kleespies et al, 1990; Linke et al, 2002) or having an increased awareness of the limits of their professional ability to prevent suicide (Goldstein & Buongiorno, 1984; Gulfi et al, 2010; Ting et al, 2006). Other studies detected increased acceptance of suicide itself (Finlayson & Graetz Simmonds, 2016) or feelings of understanding or acceptance of suicide as an option (Rothes, Scheerder, Van Audenhove, & Henriques, 2013; Ting et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Although the methodologies in the quantitative studies were heterogeneous, making comparisons difficult, 13 studies (total n = 717) utilized the Impact of Event Scale (IES or IES‐R, Horowitz, Wilner, & Alvarez, 1979; Weiss & Marmar, 1996) and reported that between 12% and 53% of their samples recorded clinically significant scores in the time immediately following the suicide (see Table 2). Of the other quantitative and mixed‐method studies, Finlayson and Graetz Simmonds (2016) included 12 items in their study questionnaire to capture intensity of emotions and reported that sadness was rated most highly, followed by shock, helplessness, anger, and pain. Gulfi, Castelli Dransart, Heeb, and Gutjahr (2010) used nine items from an adapted Long‐term Emotional Impact Scale and reported low to moderate impact overall, with increased sensitivity to signs of risk and increased anxiety when working with suicidal patients being the highest rated items.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations